Improving anaerobic co-digestion of different residual biomass sources readily available in Colombia by process parameters optimization (2023)
In the framework of sustainable development, there is an increasing need to assess, model, and optimize the implementation of renewable energy technologies such as the anaerobic co-digestion of different organic residues. This work studied the influence of some independent parameters on the production of biogas through anaerobic co-digestion of specific organic residues widely available in Colombia (pig manure -PM-, sewage sludge –SS–, organic fraction of municipal solid waste -OFMSW-, residues from the bottled fruit drinks industry -RBFDI-, and cocoa industry residue -CIR-). The Biochemical Methane Potential (BMP) of different mixtures was assessed through a Box-Behnken experimental design, where the parameters were: volatile solids content (0.5, 1.25 and 2 g VS), C/N ratio (25, 35 and 45), and nitrogen source (0% for only SS, 50% both residues PM and SS, and 100% if only PM). The results allowed empirical model building by using second-order polynomial and MARSplines. According to the maximization, the best mixture for biogas production is the one containing RBFDI, OFMSW, and SS, a C/N ratio of 40 and 0.5 g VS; the estimated production was around 382.17 ml CH4 g-1 VS, MARSplines demonstrated to have the best predictions values and the highest determination coefficient (94–97%). Moreover, it was evidenced that the content of g VS is a critical variable on the methane production, C/N ratio must be in average values, and both nitrogen sources are suitable to be used in the co-digestion process depending on the availability of the area of interest. © 2020 Elsevier Ltd